2021
DOI: 10.1109/tc.2020.3022933
|View full text |Cite
|
Sign up to set email alerts
|

DMRlib: Easy-Coding and Efficient Resource Management for Job Malleability

Abstract: Process malleability has proved to have a highly positive impact on the resource utilization and global productivity in data centers compared with the conventional static resource allocation policy. However, the non-negligible additional development effort this solution imposes has constrained its adoption by the scientific programming community. In this work, we present DMRlib, a library designed to offer the global advantages of process malleability while providing a minimalist MPI-like syntax. The library i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Malleability in MPI: Dynamic resource management in MPI has been studied intensively over the last years, usually under the umbrella term of "malleability". Since then, multiple frameworks have been created to support malleability in MPI applications [4,14,11,6,8]. These frameworks used different techniques and APIs to achieve malleability.…”
Section: Related Work Mpi 2's Dynamic Process Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Malleability in MPI: Dynamic resource management in MPI has been studied intensively over the last years, usually under the umbrella term of "malleability". Since then, multiple frameworks have been created to support malleability in MPI applications [4,14,11,6,8]. These frameworks used different techniques and APIs to achieve malleability.…”
Section: Related Work Mpi 2's Dynamic Process Modelmentioning
confidence: 99%
“…These frameworks used different techniques and APIs to achieve malleability. For example, some authors propose process splitting and merging for expansion and shrinking of the application [4,8]. Other authors start new processes while keeping the old, existing processes running [14].…”
Section: Related Work Mpi 2's Dynamic Process Modelmentioning
confidence: 99%
“…To date, malleability is infrequently used by applications, as described in Hori et al (2021) and Bernholdt et al (2018). Although checkpoint/restart (C/R) techniques exhibit similar behaviour and can ease the adoption of malleability in codes, they have exceedingly high reconfiguration times (Iserte et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The application of malleability has shown an approximately 20% reduction of the makespan in Posner and Fohry (2021). Furthermore, Iserte et al (2020) demonstrated the ways to use it to reduce makespan by approximately 4x when combined with malleability techniques, whereas Iserte and Rojek (2019) showed its impact on energy efficiency improving approximately 2.4x in GPU-capable workloads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation